Tyrosine kinases in nodal peripheral T-cell lymphomas - Piccaluga, Pier Paolo; Cascianelli, Chiara; Inghirami, Giorgio (Frontiers in Oncology, 2023)
Nodal peripheral T-cell lymphomas (PTCL) are uncommon and heterogeneous tumors characterized by a dismal prognosis. Targeted therapy has been proposed. However, reliable targets are mostly represented by a few surface antigens (e.g., CD52 and CD30), chemokine receptors (e.g., CCR4), and epigenetic gene expression regulation. In the last two decades, however, several studies have supported the idea that tyrosine kinase (TK) deregulation might be relevant for both the pathogenesis and treatment of PTCL. Indeed, they can be expressed or activated as a consequence of their involvement in genetic lesions, such as translocations, or by ligand overexpression. The most striking example is ALK in anaplastic large-cell lymphomas (ALCL). ALK activity is necessary to support cell proliferation and survival, and its inhibition leads to cell death. Notably, STAT3 was found to be the main downstream ALK effector. Other TKs are consistently expressed and active in PTCLs, such as PDGFRA, and members of the T-cell receptor signaling family, such as SYK. Notably, as in the case of ALK, STAT proteins have emerged as key downstream factors for most of the involved TK.